2019
DOI: 10.3390/ijms21010175
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy is Activated In Vivo during Trimethyltin-Induced Apoptotic Neurodegeneration: A Study in the Rat Hippocampus

Abstract: Trimethyltin (TMT) is an organotin compound known to produce significant and selective neuronal degeneration and reactive astrogliosis in the rodent central nervous system. Autophagy is the main cellular mechanism for degrading and recycling protein aggregates and damaged organelles, which in different stress conditions, such as starvation, generally improves cell survival. Autophagy is documented in several pathologic conditions, including neurodegenerative diseases. This study aimed to investigate the autoph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 80 publications
0
8
0
Order By: Relevance
“…In this study, we employed the Simoa assay to measure serum and CSF NfL levels, evaluated the potential of NfL as a peripheral biomarker of CNS toxicity, and compared the sensitivities of typical neurotoxicity endpoints such as nervous symptoms and histopathology in rat neurotoxicity models induced by trimethyltin (TMT), kainic acid (KA), and MK-801. TMT induces injury in CNS neurons and several nervous symptoms ( Balaban et al , 1988 ; Bushnell and Evans, 1985 ; Ceccariglia et al , 2020 ; Crofton et al , 1990 ; Ogata et al , 2015 ). KA, an agonist of kainate glutamate receptor subtypes, causes glutamate excitotoxicity in rodents ( Zheng et al , 2011 ), and KA treatment is one of the most reliable models for temporal lobe epilepsy ( Bertoglio et al , 2017 ; Levesque and Avoli, 2013 ; Zheng et al , 2011 ).…”
mentioning
confidence: 99%
“…In this study, we employed the Simoa assay to measure serum and CSF NfL levels, evaluated the potential of NfL as a peripheral biomarker of CNS toxicity, and compared the sensitivities of typical neurotoxicity endpoints such as nervous symptoms and histopathology in rat neurotoxicity models induced by trimethyltin (TMT), kainic acid (KA), and MK-801. TMT induces injury in CNS neurons and several nervous symptoms ( Balaban et al , 1988 ; Bushnell and Evans, 1985 ; Ceccariglia et al , 2020 ; Crofton et al , 1990 ; Ogata et al , 2015 ). KA, an agonist of kainate glutamate receptor subtypes, causes glutamate excitotoxicity in rodents ( Zheng et al , 2011 ), and KA treatment is one of the most reliable models for temporal lobe epilepsy ( Bertoglio et al , 2017 ; Levesque and Avoli, 2013 ; Zheng et al , 2011 ).…”
mentioning
confidence: 99%
“…Within DG, the expression of NTPDase2 decreased in presynaptic boutons innervating neurons in PoDG ( Amaral et al, 2007 ), whereas the recovery occurred in the PoDG, SGL, and at astrocytic sheats traversing the GrDG . As described in several recent papers, exposure to TMT induces selective neuronal death ( Ceccariglia et al, 2019 ) and consequent massive increase in extracellular ATP, which attracts microglia and initiates inflammatory responses of astrocytes ( Davalos et al, 2005 ), mainly via P2X7 receptors ( Buffo et al, 2010 ). From 2-dpi onwards, PoDG became populated with highly reactive astrocytes, which express iNOS, C3, NFkB, and P2X7R, and secrete pro-inflammatory cytokines IL-1β, IL-6, IFN-γ, and TNF-α in the parenchyma ( Dragic et al, 2021b ; Latini et al, 2010 ; Little et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Lattanzi et al (2007) reported an increase in autophagyassociated genes using microarray analysis in TMT-treated PC12 cells with respect to untreated controls. Very recently Ceccariglia et al (2019) investigated the autophagy status through the analysis of LC3, p62, and Beclin 1 as main regulatory markers in the rat hippocampus at different time points after TMT administration. Authors concomitantly evaluated the main apoptosis pathways to check for a potential correlation between the autophagy status and apoptosis machinery.…”
Section: Autophagy In Tmt-induced Neurotoxicitymentioning
confidence: 99%